„Dissertationen Online” - The ETD Project of the German Learned Societies - Diepold, Peter (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
In 1996 four German learned societies - comprising the fields of chemistry, informatics, mathematics, and physics - signed a formal agreement to collaborate in developing and using digital information and communication technologies (ICT) for their members, scientific authors and readers.